2020
DOI: 10.1002/ange.201914953
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Fate of Formaldehyde in Methanol‐to‐Hydrocarbon Reaction: In Situ Synchrotron Radiation Photoionization Mass Spectrometry Study

Abstract: HCHO has been confirmed as an active intermediate in the methanol‐to‐hydrocarbon (MTH) reaction, and is critical for interpreting the mechanisms of coke formation. Here, HCHO was detected and quantified during the MTH process over HSAPO‐34 and HZSM‐5 by in situ synchrotron radiation photoionization mass spectrometry. Compared with conventional methods, excellent time‐resolved profiles were obtained to study the formation and fate of HCHO, and other products during the induction, steady‐state reaction, and deac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…The researchers studied the behavior of HCHO in MTH by adding HCHO into the reactants, and found that the addition of HCHO can significantly increase the selectivity to aromatics 15,20,21 , and accelerate catalyst deactivation 22,23 . In our previous work, the critical role of HCHO in the mechanisms of aromatic formation was confirmed with the excellent time-resolved profiles obtained by in situ synchrotron radiation photoionization mass spectrometry (SR-PIMS) 24 .…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…The researchers studied the behavior of HCHO in MTH by adding HCHO into the reactants, and found that the addition of HCHO can significantly increase the selectivity to aromatics 15,20,21 , and accelerate catalyst deactivation 22,23 . In our previous work, the critical role of HCHO in the mechanisms of aromatic formation was confirmed with the excellent time-resolved profiles obtained by in situ synchrotron radiation photoionization mass spectrometry (SR-PIMS) 24 .…”
mentioning
confidence: 59%
“…In this work, in situ SR-PIMS (Supplementary Fig. 1) was further utilized to explore the formation and function of HCHO in MTH over Ga-modified HZSM-5 24 . To alleviate the secondary reactions of HCHO, a 2 Torr pressure was applied to the catalytic reactor.…”
Section: Resultsmentioning
confidence: 99%
“…In existing literature, this deactivation phenomenon has often been associated with the detrimental role of formaldehyde (HCHO) or its derived oxymethylene species, which promote the generation of aromatics-based coke precursors and expedite catalyst deactivation. 17,30,52,70,71 HCHO is a by-product in MTO catalysis, resulting from the disproportionation of methanol (2CH 3 OH → CH 4 + HCHO). 30 To mitigate the adverse impact of HCHO, metallic scavengers such as Y 2 O 3 are typically combined with zeolites to form bifunctional catalytic systems, enhancing the reaction's durability.…”
Section: Resultsmentioning
confidence: 99%
“…In existing literature, this deactivation phenomenon has often been associated with the detrimental role of formaldehyde (HCHO) or its derived oxymethylene species, which promote the generation of aromatics-based coke precursors and expedite catalyst deactivation. 17,30,52,70,71 HCHO is a by-product in MTO catalysis, resulting from the…”
Section: Mto Catalytic Performance Over the Bifunctional Zeolite/ Zeo...mentioning
confidence: 99%